PELANGGARAN KESANTUNAN BERBAHASA INDONESIA DALAM KOMENTAR VIDEO KLIP LAGU BAD ASS KARIN NOVILDA DI YOUTUBE EDISI FEBRUARI 2017 - Dista Anggry Prameswari; Sri Budi Astuti (Buana Bastra, 2022)
This research is based on a video clip song Bad Ass different from other video clips. Bad Ass’s video clip is a new video clip with an unflattering scene concept. This study aims to describe the violation of language politeness that includes modesty tact maxim, approbation maxim, modestky maxim, agreement maxim, generosity maxim, and sympath maxim in the comments video klip song Bad Ass Karin Novilda on Youtube. The data in this study are words or phrases in the form of comments that contain violations of language modesty tact maxim, approbation maxim, modestky maxim, agreement maxim, generosity maxim, and sympath maxim. Sources of data in this study is a commentary from the video clip song Bad Ass by Karin Novilda in Social Media Internet that is Youtube edition of February 2017. The techniques of collecting data of this research is technique of free capability and technique of note. Data analysis technique used in this research is descriptive qualitative. Based on the results of data analysis can be concluded that the violation of politeness language in comments video clip song Bad Ass Karin Novilda on Youtube February 2017 edition. At the modesty maxim is able to maximize the benefits of others. The approbation maxim is able to minimize reproaches in the other side. The maxim agreement is indicated by the agreement between the self and the other person. The maxim sympathy is shown to have as much sympathy as possible in the other side. The maxim generosity is shown to be generosity on the other side. Maxim of praise is able to maximize praise on the other side.